THE INFLUENCE OF GLOBAL MIGRATION POLICIES ON THE RIGHTS OF INTERNALLY DISPLACED PERSONS - PS, Renjini; Philipose, Geni (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Internally Displaced Persons (IDPs) are a substantial but frequently neglected section of the global displaced population. IDPs, unlike refugees, remain within their country's boundaries and rely on national frameworks for protection, which are frequently affected by global migration policy. This article investigates how international migration policies, such as asylum limits, border security measures, and financial allocation, indirectly affect the rights and well-being of IDPs. While frameworks like the Guiding Principles on Internal Displacement (1998) provide a foundation for IDP protection, their nonbinding character leads to varied implementation across countries. In addition, global migration strategies that prioritize external migration control frequently result in a disproportionate allocation of resources, leaving IDPs out. This paper evaluates the socioeconomic and legal ramifications of these policies on IDPs through case studies from Syria, Venezuela, and Nigeria. It also argues for the inclusion of IDP rights in global migration governance to create a more equal and effective response to internal displacement. By addressing these shortcomings, international and national authorities can contribute to a more holistic and rights-based approach to displacement.